Posted by Rihanna on Monday, January 17, 2011 at 8:51pm.
x - 2y = 10
3x - y = 0
eliminate y by multiplying 3x - y = 0 by -2
-2(3x - y = 0) = -6x + 2y = 0
ADD the 2 equations
x - 2y = 10
-6x + 2y = 0
-5x + 0 = 10
-5x = 10
x = -2
substitute x = -2 in x - 2y = 10, to find y
x - 2y = 10
-2 - 2y = 10
-2y = 12
y = -6
check x = -2, y = -6
3x - y = 0
3(-2) - -6 = 0
-6 + 6 = 0
0 = 0
Oh so You have to multiply it by -2 because the first equation also uses -2 and you have to cancel them out that way right?
So if its - and + that means you have to add the equations. If its - and - that means you have to subtract and if it's + and + that also means you have to subtract right?
How did you get -2 as an answer?
Did you divide 5x by 5 and 10 by five to get 2?
You lost me right here:
How did you do this?
x - 2y = 10
-2 - 2y = 10
-2y = 12
y = -6
How did you get the second line?
-2 - 2y = 10?
And at the end you went 0 = 0
so they have to equal to zero always?
How did you get -2 as an answer?
Did you divide 5x by 5 and 10 by five to get 2? YES
You lost me right here:
How did you do this?
x - 2y = 10
-2 - 2y = 10
-2y = 12
y = -6
How did you get the second line?
-2 - 2y = 10?
to find the value of y, since you know x = -2, you plug x = -2 into either equation and solve for y
the second line is from plugging -2 in for x in the equation x - 2y = 10
x = -2
x - 2y = 10
-2 - 2y = 10
-2y = 12
y = -6
yes, when you check, both sides will equal 0 if you are correct